GW24-e1886 Hepatocyte growth factor regulates glycogen synthase kinase-3beta and AMP-activated protein kinase in cardiomyocytes under diabetic conditions. (1st October 2013) - Cairong, Li; Zheng, Hai-tao; Zhao, Xin-yuan; Gan, Shou-yi; Zeng, Ling-yong; Huang, Hong-Xia; Li, Bing; Wang, Jiang-Hong; Ge, Xiong; Huang, Jun; Feng, Guang-rui; Liu, Liang; et al.
Abstract : Objectives: To study the effect of hepatocyte growth factor (HGF) on glycogen synthase kinase-3β (GSK-3β) and AMP-activated protein kinase (AMPK) activity in cardiomyocytes under diabetic conditions. Methods: We used high concentration glucose and HGF to stimulate the cultured rats cardiomyocytes. To investigate the direct effect of GSK-3β on cardiomyocytes, we changed its activity by transient transfection with three kinds of GSK-3β mutant plasmids, nonphosphorylatable constitutively active mutant of GSK-3β(S9A-GSK-3β), catalytically inactive GSK-3β (KM-GSK-3β) and adenoviral vectors encoding wild-type (WT- GSK-3β). The protein expression of GSK-3β, pGSK-3β, AMPK, pAMPK was determined by Western blot. The levels of monocyte chemoattractant protein-1(MCP-1) and intercellular adhesion molecule-1 (ICAM-1) in the supernatants were determined by enzyme-linked immunosorbant assay (ELISA). Results: HGF increased the expression of pGSK-3β and pAMPK protein in cardiomyocytes induced by high glucose. C-Met inhibitor completely inhibited the phosphorylation of GSK-3β protein, PI3K, PKC and p38MAPK inhibitors could partially inhibit the phosphorylation of GSK-3β protein, while JAK2 and ERK1/2 inhibitors had no effect. In contrast, ectopic expression of S9A- GSK-3β abolished the HGF regulatory action on MCP-1 and ICAM-1 protein expression. Activation of MAPK by HGF leads to the rapid and transient phosphorylation of cAMP response element-binding protein (CREB). Conclusions: These results support the conclusion that regulation of cardiomyocytes metabolism by HGF is mediated by activation of the AMPK/GSK-3β pathway. HGF-induced downregulation of MCP-1 and ICAM-1 protein involves activation of the C-Met, PI3K, PKC and p38MAPK pathway and requires the activity of early GSK-3β. These findings suggest that inhibitory phosphorylation of GSK-3β at Ser-9 is required for HGF inhibition of STAT3 in cardiomyocytes induced by high glucose. Acknowledgements: This work was supported by the National Nature Science Foundation of China (NSFC) Grant 81000576 to Fei Cai, Foundation of Department of education of Hubei Province of China Q20112804, Q20112801 to Fei Cai and Cai-rong Li.